Penyelesaian Sengketa Kontrak Konstruksi Internasional Melalui Arbitrase ICSID - Sudarsono Sudarsono; Sarwono Hardjomuljadi; Sami’an Sami’an; Anik Kunantiyorini (Jurnal Impresi Indonesia, 2026)
This study aims to examine the settlement of investment disputes between the government and foreign investors through the ICSID institution and the mechanism for implementing its decisions in Indonesia. The research method used is normative legal research with a regulatory approach and a conceptual approach. ICSID (International Centre for Settlement of Investment Disputes) is based on an international agreement that establishes an autonomous and independent system for the settlement of foreign investment disputes. The ICSID's performance does not serve as a mediator that reconciles the parties; rather, it provides an institutional and procedural framework for independent conciliation commissions and arbitration tribunals set up specifically for each dispute case. In this case, ICSID only provides dispute resolution facilities based on two sets of procedural rules, namely the provisions of the ICSID Convention along with the ICSID Regulations/Rules, as well as the ICSID Additional Facilities Rules. Furthermore, the implementation of ICSID institutional decisions in Indonesia refers to Law No. 30 of 1999 which stipulates that the authority to recognize and implement international arbitral awards lies with the Central Jakarta District Court, with a procedure that must be preceded by an application from the party concerned.